Occurrence and Distribution of Aflatoxin in Maize from Selected Counties, Eastern Region, Kenya - Jacob, Nicholas M.; Wandiga, Shem O.; Kariuki, David K.; Madadi, Vincent O. (Journal of Agricultural Policy, 2020)
Purpose: The study aimed to assess the occurrence and distribution of aflatoxin contamination on dry maize in different types of stores in Meru, Embu, Isiolo, Makueni and Machakos Counties of Eastern region of Kenya. Methodology: Automatic spear sampler was used to collect maize samples from each bag at even intervals. 280 maize samples were collected from 29 stores in five Counties. 100 g of each maize sample was ground, resampled into 50g, blended, extracted, centrifuged, filtered and a quantified for Aflatoxin B1, B2, G1 and G2. Samples were prepared and extracted with methanol/water. The bulky of the samples were analyzed with enzyme-linked immunoassay test kits. Confirmation of positive samples was done with high performance liquid chromatography (HPLC) coupled with fluorescence detector. Data analysis was done with SPSS and Microsoft excel. Findings: Maize samples from Counties in eastern region of Kenya had significantly high levels of (93.10%) aflatoxin contamination. The mean values for aflatoxin B1, B2, G1 and G2 were: 50.08± 4.42, 17.26±1.08, 30.17±2.06 and 10.54± 1.52 (ng/g) in that order. Only nine samples had total aflatoxin within the accepted limit for human consumption of 15 ng/g. The highest total aflatoxin contamination recorded was 198.45ng/g in Makueni county and the lowest recorded was 8.76ng/g in Embu county. Makueni and Embu had mean values for aflatoxin B1, B2, G1 and G2 being (83.07±7.53, 22.15± 1.36, 49.38±3.11, 20.52± 0.70 ng/g) and (18.71 ±2.63, 8.07 ±0.64, 17.02 ±1.38, 8.86 ±1.62 ng/g). Makueni NCPB depot had the highest mean contamination with aflatoxin B1 of 92.67± 5.78 ng/g and Embu had the lowest with 6.26 ± 4.14 ng/g. All the county markets recorded high aflatoxin B1 contamination with exception of Embu county which had a mean of 4.0 ±0.84, Makueni (83.67± 10.42 ng/g), Isiolo (51.27± 32.29 ng/g), Meru (46.02± 23.88 ng/g) and Machakos (36.34± 26.27 ng/g). The stores had aflatoxin load varied from on store to the other and county to county. Unique contribution to theory, policy and practice: The counties in the region had high occurrence and distribution of aflatoxin B1, B2, G1 and G2 in maize in all stores where samples were picked. Location for maize stores should be in areas with low levels of carbon dioxide because mycotoxins are produced under aerobic conditions. The design for maize threshing machines should not course shocks, breakage and cracks on maize grains to decrease chances of mycotoxins infestation during their storage.